2010
DOI: 10.1530/eje-09-0416
|View full text |Cite
|
Sign up to set email alerts
|

Overweight is associated with impaired β-cell function during pregnancy: a longitudinal study of 553 normal pregnancies

Abstract: Objective: To monitor b-cell function and insulin sensitivity longitudinally in a large cohort of pregnant women to elucidate mechanisms that influence glycemic control in pregnancy. Design and methods: Five hundred and fifty-three pregnant Scandinavian women underwent 75 g oral glucose tolerance test (OGTT) at weeks 14-16 and 30-32. Insulin sensitivity (Matsuda index) and b-cell function (ratio of AUC insulin to AUC glucose , AUC ins/glc ) were calculated from 520 complete tests, and subsequently b-cell funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…The patients who developed GDM in the 3rd trimester also had significantly higher HOMA-IR, which emphasizes the role of increased insulin resistance against the background of enormous tissue insulin demands in the development of late-onset GDM. Our findings are consistent with the results of other studies (44,45,46) showing unchanged AUC Ins /AUC Glu index, but an inadequate insulin compensation for decreased insulin sensitivity in women with GDM. We should also mention that the number of patients with a normal OGTT result at the 1st visit, but later diagnosed as having GDM, was much higher than expected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The patients who developed GDM in the 3rd trimester also had significantly higher HOMA-IR, which emphasizes the role of increased insulin resistance against the background of enormous tissue insulin demands in the development of late-onset GDM. Our findings are consistent with the results of other studies (44,45,46) showing unchanged AUC Ins /AUC Glu index, but an inadequate insulin compensation for decreased insulin sensitivity in women with GDM. We should also mention that the number of patients with a normal OGTT result at the 1st visit, but later diagnosed as having GDM, was much higher than expected.…”
Section: Discussionsupporting
confidence: 93%
“…As a decrease in b-cell function is to some degree masked by physiological insulin resistance during pregnancy, the DI has been developed to adjust for compensatory high insulin response to a decreased insulin sensitivity (31). As it was demonstrated by Qvigstad et al (44), DI seems to be markedly lower in GDM subjects and this reduction may be noticeable at the beginning of the 2nd trimester when the patients are classified as glucose tolerant. In our study, the patients with both earlier and late onset of GDM also demonstrated a significant decrease in the surrogate markers of b-cell function, although an index of the early-phase insulin release (AUC Ins30 /AUC Glu30 ) did not differ markedly between the women with and without GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose was measured from frozen serum samples at antenatal visit GA 30-32 weeks, with the hexokinase method at an accredited clinical chemistry laboratory at Oslo University Hospital, Rikshospitalet (Hitachi Modular P800 with reagents from Roche) and results are used further for this study. The median difference in glucose values for the 300 women at antenatal visit GA 30-32 weeks between on-site measurements (16) …”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…The effects on pregnant women are such as eclampsia, placental abruption, cerebrovascular accident, infection of urologic and reproductive system, prolonged labor, postpartum hemorrhage. And the effects on infants are like macrosomia, malformation fetus, fetal death [6][7][8] . The IR refers to an impaired biological response to either exogenous or endogenous insulin, implying the depreciation of the insulin, showing the decreases of sensitivity and the use of glucose of circumference organization, especially muscle and fat tissue.…”
Section: Dicussionmentioning
confidence: 99%